FAKTOR - FAKTOR YANG MEMPENGARUHI PELAKSANAAN PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI PEDESAAN (PNPM MPD) (STUDI KASUS : KEGIATAN SIMPAN PINJAM PEREMPUAN DI NAGARI TANJUNG BETUNG KABUPATEN PASAMAN) - Ema Fitri Lubis (UIR Press, 2018)
This research aims to find out the factors that influence implementation activities of the SPP (Women’s Saving and Loans) in Nagari Tanjung Betung, Regency of Pasaman. The method used in this research is descriptive qualitative research, data collection by means of interviews, observation, and documentation with UPK Team and community users group of SPP (Women’s Savings and Loans) in Nagari Tanjung Betung. The results showed that in terms of the interests that are affected by the policy are enshrined the importance either for UPK, implementing areas, and SPP funds users, still lack of the benefits and changes in the gain due to a goal from inappropriate programs, namely on Non RTM, more prioritize the smooth repayment compared the concept of empowerment, taking and executing layout policies were in accordance with the mechanisms and provisions laid down. Resources adequate in terms of quality but felt less in terms of quantity. Obstacles encountered are lacking of coordination and communication so that an understanding of the purpose of the SPP program to the community have not precise. Even so, with the construction will attempt by those who are still less so that there is no significant development for the efforts.